(untitled) (Research, Society and Development, 2020)
The objective of the present experiment was to evaluate the effects of including the essential oil of copaiba and oregano as a possible replacement for synthetic butylated hydroxytoluene (BHT) additives in fish meat ball. PH, cooking loss, texture, color, sensory acceptability and chemical composition were evaluated. The addition of oregano essential oil had an effect on the color of the fish meat ball (P <0.05), showing better results for a * and Hue compared to BHT, and b * and Croma compared to the control (COM). In addition, the essential oils of copaiba and oregano showed the lowest water losses by cooking and the essential oil of oregano improved the aroma of the fish meat ball (P <0.05). The treatments had no effect (P> 0.05) on the chemical composition of the fish meat ball. The essential oils of copaiba and oregano are promising natural antioxidants to increase the useful life of fish by-products, in addition to being a viable solution to replace the synthetic antioxidant BHT, bringing benefits to its commercialization.